Stoichiometry-dependent local instability in MAPbI3 perovskite materials and devices. Issue 46 (12th November 2018) - Kumar, Vikas; Barbé, Jérémy; Schmidt, Whitney L.; Tsevas, Konstantinos; Ozkan, Buse; Handley, Christopher M.; Freeman, Colin L.; Sinclair, Derek C.; Reaney, Ian M.; Tsoi, Wing C.; Dunbar, Alan; Rodenburg, Cornelia
Abstract : Organometallic perovskite materials based on MAPbI3 achieve photovoltaic efficiencies as high as 22% for solar cells; however, the long-term stability of these perovskite materials is still a hurdle for applications. Abstract : Organometallic perovskite materials based on MAPbI3 achieve photovoltaic efficiencies as high as 22% for solar cells; however, the long-term stability of these perovskite materials is still a hurdle for applications. Here, we report the air and charge induced instabilities of MAPbI3 perovskite materials with different local stoichiometry using Secondary Electron Hyperspectral Imaging (SEHI). We find that individual grains which do not have the ideal ABX3 stoichiometry degrade faster than stoichiometric grains. We also observe that the degradation pathways depend on the local stoichiometry. Non-stoichiometric grains (with excess MAI) degrade from the centre of the grain and further degradation moves towards the grain boundary, whereas in stoichiometric grains degradation sets in at the grain boundary. We further use deliberately high doses of electron beam exposure to highlight the presence of local non-stoichiometry in device cross-sections of bias degraded devices which pinpoints different onset locations of degradation, depending on the local stoichiometry. These results, therefore, show that precise control of local stoichiometry is required to improve the stability of MAPbI3 and thus the lifetime of perovskite solar cells.